The Effect of Horticultural Therapy on Increased Self-Esteem for Mental Disorders in the Community - Subagyo, Widyo; Wahyuningsih, Dyah (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: The increasing number of mental disorders causes various problems, so treatment and rehabilitation programs are needed to increase adaptability and prevent recurrences in the community. MATERIAL AND METHODS: This study used a quasi-experimental method with a pre-post test between the intervention and control groups. Effects of horticultural therapy on self-esteem were analysed using paired t-tests. RESULTS: The results showed a significant difference in the self-esteem scores of patients with mental disorders before and after treatment in the intervention group with horticultural therapy (p-value of 0.00). CONCLUSION: A significant difference exists in the self-esteem scores of patients with mental disorders before and after treatment in the intervention group given horticultural therapy marked. The participants in the study had various mental disorders, including schizophrenia and depression. Both schizophrenia and depression are associated with symptoms of low self-esteem. Horticultural therapy positively enhances self-esteem regardless of specific mental disorders.